Specific hydrolysis of rabbit globin messenger RNA by S1 nuclease. - Flashner, M S (1977)
S1 nuclease isolated from Aspergillus oryzae has been used to investigate the secondary structure of rabbit globin messenger RNA (mRNA). The enzyme, which is specific for single stranded nucleotides, digests globin mRNA to a limited extent, with 65-75% of the mRNA nucleotides resistant to digestion under mild conditions. This limited digestion is not due to enzyme inactivation, but rather to the normal activity of the single-strand nuclease. The reaction was studied as a function of temperature, salt and enzyme concentration. Analysis of the products of digestion on 20% acrylamide- 7M urea slab gels reveals a stable pattern of unique fragments ranging in size from 9 to 71 nucleotides. Separated alpha and beta globin mRNAs show similar, but not identical gel patterns, indicating strong structural similarities between the two species. The high degree of nuclease resistance, along with the fragment patterns seen on polyacrylamide gels, gives evidence to support a model of rabbit globin mRNA which contain specific, rather than random, helical structure.